Dual institution experience of nodal marginal zone lymphoma reveals excellent long‐term outcomes in the rituximab era. (22nd July 2016) - Starr, Adam G.; Caimi, Paolo F.; Fu, PingFu; Massoud, Mira R.; Meyerson, Howard; Hsi, Eric D.; Mansur, David B.; Cherian, Sheen; Cooper, Brenda W.; De Lima, Marcos J. G.; Lazarus, Hillard M.; Gerson, Stanton L.; et al.
Summary: Nodal marginal zone lymphoma (NMZL) is a rare non‐Hodgkin lymphoma that arises from mature B‐cells. We delineate outcomes, prognostic factors and treatment trends among a large cohort of patients with NMZL in the rituximab era. We identified 56 such patients treated at our institutions. The majority presented with advanced stage disease (78·6%). Over a median follow‐up of 38·2 months, median progression‐free survival (PFS) was 42·4 months and median overall survival (OS) was not reached. Kaplan–Meier estimates of OS at 120 months after diagnosis was 71·9%. High‐risk follicular lymphoma international prognostic index (FLIPI) was associated with inferior PFS. Age >60 years and elevated serum lactate dehydrogenase (LDH) were associated with inferior OS. Transformation to diffuse large B‐cell lymphoma occurred in 7 patients, 6 of who presented with advanced disease. OS was comparable to our previously reported extranodal MZL cohort. FLIPI score predicted for inferior PFS and OS when both cohorts were analysed together ( n  = 267). In summary, outcomes in NMZL are favourable with a large majority of patients surviving at 120 months. High risk FLIPI, age >60 years, and elevated serum LDH were associated with inferior outcomes.